Nanostructured vanadium dioxide thermochromic smart windows - Liu, Chang (2017)
In the recent years, thermochromic smart windows, as a category of solar control windows, provide the solutions for saving the energy usage in the buildings or vehicles. Vanadium dioxide (VO2) is considered as a promising smart window material because of its infrared-switchable optical properties, which is led by the intrinsic phase transition at a critical temperature of 68 C. The temperature stimulated thermochromic effects make VO2 as the superior candidate of energy-efficient smart windows, but the real application of VO2 continuous thin films is hindered mainly due to the low luminous transmittance (Tlum) and the insufficient solar modulation ability (ΔTsol), which are largely caused by the intrinsically high optical absorption and the unwanted high refractive index (RI). To tackle these issues, the work covered by this thesis utilizes three attempts, namely VO2 nanocomposites, grid-patterning and RI tunable anti-reflection coatings (ARC) on the basis of various VO2 substrates, to achieve largely enhanced both Tlum and ΔTsol.